Evaluasi Pengaruh Kebijakan Anti-Korupsi terhadap Efektivitas Penyaluran dan Program Bantuan Pendidikan di Indonesia - Huntua, Hariyanto; Moonti, Roy Marthen; Bunga, Marten; Kasim, Muslim A. (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Corruption in the disbursement of educational aid funds poses a serious challenge that undermines the effectiveness of education policies in Indonesia, particularly within programs such as the Indonesia Smart Program (PIP) and the Family Hope Program (PKH). Irregularities in fund management, weak supervision, and the lack of transparency and accountability have led to unequal distribution of aid and a decline in the quality of educational services. This study aims to evaluate the impact of anti-corruption policies on the effectiveness of educational fund distribution through a normative approach using secondary data. The findings indicate that the implementation of anti-corruption policies, supported by the digitalization of financial systems, public participation, and institutional reform at the local level, has a significant effect in reducing the misuse of educational funds. However, the effectiveness of these policies heavily depends on political commitment, the capacity of supervisory institutions, and public legal awareness. Therefore, synergy between law, technology, a culture of integrity, and community participation is essential to building clean and equitable education governance in pursuit of Indonesia Emas 2045.